Strategi Penataan Pedagang Kaki Lima dalam Meningkatkan Keindahan dan Ketahanan Infrastruktur Kota di Kabupaten Sinjai - Melisa Melisa; Mochamat Nurdin; Rajamemang (Universitas Mbojo Bima, 2025)
The strategy for arranging Street Vendors (PKL) in North Sinjai District, Sinjai Regency, is one of the strategic efforts of the Sinjai Regency government in creating an orderly, safe, comfortable, clean, and aesthetic urban environment. This research aims to analyze the street vendor arrangement strategy implemented in the area and the resilience of city infrastructure in Sinjai Regency. A qualitative research method with a descriptive approach was used in this study. Data was collected through observation, in-depth interviews involving informants from various sources based on characteristics and existing answers, and observation at the research location. The strategy for arranging Street Vendors (PKL) in Sinjai Regency focuses on four main indicators, namely: (1) Orderliness: Through enforcement and regulation of trading locations, the government strives to create order and avoid disrupting community activities and traffic flow; (2) Safety and Comfort: The lack of adequate facilities to support safety and comfort for vendors and visitors, such as the provision of vendor relocation sites, the construction of representative kiosks/stalls, and adequate sanitation facilities, is a priority in this arrangement; (3) Cleanliness: The local government has not provided adequate waste disposal facilities and has not conducted routine monitoring to ensure the environment around the street vendors remains clean and free from waste; (4) City Aesthetics: The arrangement of street vendors is carried out by considering the aspect of city aesthetics, paying attention to attractive basic elements that do not damage the city view has not been running effectively, which can be seen from several city points that look unkempt and poorly maintained. The strategy for arranging Street Vendors in North Sinjai District, Sinjai Regency, was analyzed using Geoff Mulgan's theory. Therefore, the Sinjai Regency Government must formulate a policy regulating the Arrangement of Street Vendors in North Sinjai District, Sinjai Regency, so that the implemented strategy can run effectively. Keywords: Arrangement of Street Vendors (PKL), City Beauty, City Infrastructure Resilience